Nursing Considerations for an Emerging and Enlarging Symbiosis Between Technology and Integrative Human Health: Need for a Systematized Base for Caring Science. - Dean, Patrick J. (International Journal for Human Caring, 2016)
Biotechnology and informatics/mathematics are increasingly incorporated within the human experience of the health-illness continuum, especially through implantable, injectable, and wearable technological devices and through health-prediction formulas originating from large, impersonal databases. In addition, a potential for closely approximating, and possibly combining, DNA code with binary (computer) code within the human health experience demands careful application by nurses of technological and caring-science principles--principles that call for vigilant protection of patients and research participants in technology-aided health care against accidents, sabotage, and manipulation. Even the dissemination of this published information through electronic media is subject to possible manipulation by hackers. Such vigilance also seems to call for incorporating systematization within caring science as a means to balance the equation between quantitatively oriented technology (exact mathematics) and qualitatively oriented caring science, for which system flexibility and inexact mathematics may seem appropriate. One possible way to begin to achieve a balance of this equation is to overcome a current Western gender split between a predominantly male-oriented profession of computer coders and a predominantly female-oriented profession of nurse carers. These individuals, for the most part, each possess the separate parts of a "technorganics" equation capable of a healthcare synergy never seen before.